KEDUDUKAN âLEX NE SCRIPTAâ DALAM SISTEM HUKUM INDONESIA - Gunakaya, A. Widiada (Sekolah Tinggi Hukum Bandung, 2010)
The values of Pancasila in our country does not become an ideal principle in every activity of lives. It is not used as a main basis of national law even as the source of all sources of law. The implication is that; in the level of application there are always stagnancy and resistance in the implementation and law enforcement. This is because of there is no âlex scriptaâ as a norm of positive law which regulates and can become juridical principle to ensnare an unlawful act. Whereas, âlex scriptaâ norm of law is acknowledged as the norm of law in Indonesia which derives from values of Pancasila as ârechsideeâ, âgrundnormâ, both in Pancasila and 1945 Constitution, and also judicial authority which merely gives authority to law enforcement apparatus to investigate, sue, punish, and decide an unlawful acts. In the system of law in Indonesia, the position âlex ne scriptaâ is equal to âlex scriptaâ. The consequence of law is that; âlex ne scriptaâ can replace the position of âlex scriptaâ if in the norm of positive law does notregulate unlawful acts. Related to the compilation of national law system in Indonesia, âlex ne scriptaâ plays an important role in developing law, especially in the context of determination of legal substance, implementation and law enforcement, and also law behavior.Keywords: Pancasila Â National Law System Â Implementation and Law Enforcement